(untitled) (Journal of Science and Technology, 2016)
The study sought to examine girls’ motivation for and subject preferences on the Senior High School Visual Arts programme in Ghana. Using findings based on the multi-site case study research method with direct observation and interviews, the study found that 54% of 300 girls in four schools in the Central Region made personal decisions to study Visual Arts while 34% were coerced into the programme by school Heads; only 12% were inspired or persuaded. Textiles emerged the most preferred elective subject because it involves “girl-friendly” skills and offers “female-appropriate” occupations. The Textiles-with-Graphic Design elective combination facilitates access into the fashion industry but many girls shun Picture-Making because girls generally lack the level of drawing skills required; Ceramics is “girl-friendly” except that clay easily dirties their clothes. Sculpture is the least preferred elective because it demands much energy and effort, involves using sharp tools and working of heavy materials; it is therefore an “inappropriate” subject for girls. This apparent discriminatory attitude towards some Visual Arts subjects impacts negatively on girls’ academic achievement on the programme and undermines gender equality in learning, educational and career development. Effective delivery of the Visual Arts curriculum and counselling could encourage more girls to participate fully in the programme.